STRUKTUR DAN KOMPOSISI VEGETASI SEBAGAI DASAR RESTORASI DEGRADASI HUTAN DI KAWASAN PERLINDUNGAN BLOK SINTANG PT FINNANTARA INTIGA - Edi Rustadi Setiadharma; Burhanuddin Burhanuddin; M Sofwan Anwari (Tengkawang : Jurnal Ilmu Kehutanan, 2021)
This study aims to examine the composition and structure of the vegetation in the protected forest area of PT Finnantara Intiga's Sintang block and determine the pattern of forest restoration and the types of vegetation that will be used for restoration of degraded forests. This research was conducted at PT Finnantara Intiga Sintang Block which is located in five land cover areas, of which three are reference secondary swamp forest (KPPN, KPSL and river border) and two areas are degraded forest (shrub and open land). This study uses a survey method with a line plot system. The sample was determined by means of purposive sampling. Based on the results of research data analysis, the number of species found at all levels at the KPSL location was nine species, at the KPPN location there were eleven species, at the River Border location there were eight species, at the Semak Belukar location there were seven species and at the Open Land location there were four species. In general, the horizontal structure of forest stands in damaged forest ecosystems is below the horizontal structure of natural forest stands as a reference. This shows that the level of vegetation density at the location of shrubs and open land has decreased so that forest restoration measures are needed to increase the density closer to natural forest ecosystems that have not been damaged. The pattern of forest restoration for scrub areas and open land referring to the Guidelines for Restoration in Conservation Areas (JICA, 2014) is natural succession. The pattern of forest restoration that will be implemented must take into account the physical conditions of the field and local socio-cultural considerations based on stakeholder considerations. The type of vegetation for enrichment and planting activities at the shrub location refers to the KPSL location as a reference because it tends to have similarities with the community similarity index of 52.03%. The type of vegetation for enrichment and planting activities on open land locations refers to the KPPN location as a reference because it tends to have similarities with the community similarity index of 52.17%. Keywords:  Composition, forest degradation, restoration, structureAbstrakPenelitian ini bertujuan untuk mengkaji komposisi dan struktur vegetasi di kawasan hutan perlindungan blok Sintang PT Finnantara Intiga serta menentukan pola pemulihan hutan dan jenis vegetasi yang akan digunakan untuk restorasi hutan terdegradasi. Penelitian ini dilaksanakan di PT Finnantara Intiga Blok Sintang yang terletak di lima areal tutupan lahan, dimana tiga areal sebagai hutan rawa sekunder referensi (KPPN, KPSL dan sempadan sungai) dan dua areal di hutan yang terdegradasi (semak belukar dan lahan terbuka). Penelitian ini menggunakan metode survey dengan cara jalur berpetak. Sampel ditentukan dengan cara Purposive Sampling. Berdasarkan hasil analisis data penelitian, Jumlah jenis yang ditemui di semua tingkatan di lokasi KPSL ada sembilan jenis, dilokasi KPPN ada sebelas jenis, di lokasi Sempadan Sungai ada delapan jenis, di lokasi Semak Belukar ada tujuh jenis dan di lokasi Lahan Terbuka ada empat jenis. Secara umum bentuk grafik struktur horizontal tegakan hutan pada ekosistem hutan yang mengalami kerusakan berada di bawah grafik struktur horizontal tegakan hutan alam yang menjadi referensi. Hal ini menunjukkan bahwa tingkat kerapatan vegetasi pada lokasi semak belukar dan lahan terbuka mengalami penurunan sehingga diperlukan tindakan pemulihan hutan untuk meningkatkan kerapatan mendekati ekosistem hutan alam yang belum mengalami kerusakan. Pola pemulihan hutan untuk areal semak belukar dan lahan terbuka merujuk pada Pedoman Tata Cara Restorasi di Kawasan Konservasi (JICA, 2014) adalah suksesi alami. Pola pemulihan hutan yang akan dilaksanakan harus mempertimbangkan kondisi fisik lapangan dan sosial budaya setempat berdasarkan pertimbangan stakeholder. Jenis vegetasi untuk kegiatan pengkayaan dan penanaman pada lokasi semak belukar mengacu pada lokasi KPSL sebagai referensi karena kecenderungan memiliki kemiripan dengan dengan indeks kesamaan komunitas sebesar 52,03%. Jenis vegetasi untuk kegiatan pengkayaan dan penanaman pada lokasi lahan terbuka mengacu pada lokasi KPPN sebagai referensi karena kecenderungan memiliki kemiripan dengan dengan indeks kesamaan komunitas sebesar 52,17%.Kata kunci: Degradasi hutan, komposisi, restorasi, struktur